Efektivitas Kemitraan dalam Pengembangan Agrowisata Studi Kasus di Agrowisata Bali Pulina Desa Sebatu Kecamatan Tegallalang Kabupaten Gianyar - SUDEWA, PANDE KOMANG HARRY; DARMAWAN, DWI PUTRA; WIDHIANTHINI, WIDHIANTHINI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Effectiveness of  Agrit ourism Development  in The Case of  Bali Pulina Agrit ourism ,  Sebatu Village,  Tegallalang District ,  Gianyar Regency Bali Pulina Agritourism is an agritourism business that partners with farmers, especially coffee farmers. The partnership between Bali Pulina Agritourism and the  Gunung Catur coffee farmers is only based on trust without any legal agreement specifying each party’s rights and obligations. In general, a partnership without legal agreement may become detrimental to both parties. This study looks at the effectiveness of the partnerships and the influencing faktors in order to establish a sustainable partnership. Respondents involved in this study include respondents for census and respondents for purposive sampling. The method used in this study is Interpretive Structural Modeling (ISM) method. The result shows the effectiveness level of partnership is 76,30%, which is in the effective category. The four main factors that influence the partnership effectiveness include the decreasing number of farmers and the lack of infrastructure, cooperatives, and tourism actors. It is recommended that Bali Pulina Agritourism and Gunung Catur Coffee Farmers develop a legal partnership agreement for a sustainable partnership.